EACVI appropriateness criteria for the use of cardiovascular imaging in heart failure derived from European National Imaging Societies voting. (29th April 2016) - Garbi, Madalina; Edvardsen, Thor; Bax, Jeroen; Petersen, Steffen E.; McDonagh, Theresa; Filippatos, Gerasimos; Lancellotti, Patrizio; Fox, Keith; Sechtem, Udo; Bengel, Frank; Maurer, Gerald; Zamorano, Jose Luis; et al.
Abstract: This paper presents the first European appropriateness criteria for the use of cardiovascular imaging in heart failure, derived from voting of the European National Imaging Societies representatives. The paper describes the development process and discusses the results.